2009
DOI: 10.1136/pgmj.2007.066902
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the history obtained by patient-completed questionnaires with doctors’ standard notes for patients with acute abdominal pain

Abstract: Patient-completed questionnaires can be used to obtain a more accurate history than junior doctors for most patients admitted with acute abdominal pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…This has also been reported in studies done in high, middle and lowincome countries. Studies in the US, Wales, and the UK have shown that medical records have poorly documented general symptoms, gynaecological history, treatment side effects, smoking history and drug allergies [16,22,23]. Furthermore, the confidential enquiries to maternal deaths in the UK have also been reported to face challenges in obtaining medical record and short reports, especially from general practitioners [24].…”
Section: Comprehensiveness Of the Narrative Summaries And Action Plansmentioning
confidence: 99%
“…This has also been reported in studies done in high, middle and lowincome countries. Studies in the US, Wales, and the UK have shown that medical records have poorly documented general symptoms, gynaecological history, treatment side effects, smoking history and drug allergies [16,22,23]. Furthermore, the confidential enquiries to maternal deaths in the UK have also been reported to face challenges in obtaining medical record and short reports, especially from general practitioners [24].…”
Section: Comprehensiveness Of the Narrative Summaries And Action Plansmentioning
confidence: 99%
“…This is true in high, middle and low income countries. Studies in the US and Wales, UK have shown that medical les have poorly documented general symptoms, gynaecological history, treatment side effects, smoking history and drug allergies (16,22,23). Furthermore the con dential enquiries to maternal deaths in the UK have also been reported to face challenges obtaining medical record and short reports especially from General Practitioners (24).…”
Section: Comprehensiveness Of the Narrative Summaries And Action Plansmentioning
confidence: 99%
“…This study con rms that MDSR systems are constrained by poorly prepared narrative summaries lacking important information. Studies in the US and Wales, UK have shown that medical les have poorly documented general symptoms, gynaecological history, treatment side effects, smoking history and drug allergies (16,22,23). This has direct negative impact on the comprehensiveness of summaries abstracted from such documentation.…”
Section: Comprehensiveness Of the Narrative Summaries And Action Plansmentioning
confidence: 99%